Exploration in the Presence of Mother in Typically and Non-typically Developing Pre-walking Human Infants - Frostig, Tzviel; Alonim, Hanna; Scheingesicht, Giora; Benjamini, Yoav; Golani, Ilan (Frontiers in Behavioral Neuroscience, 2020)
In previous phenotyping studies of mouse and rat exploratory behavior we developed a computational exploratory data analysis methodology including videotaping, tracking, preparatory methods for customized data analysis, a methodology for improving the replicability of results across laboratories, and algorithmic design for exposing the natural reference places (origins) used by animals during exploration. We then measured the animals' paths in reference to these origins, revealing robust, highly replicable modules termed excursions, which are performed from the origin into the environment and back to the origin. Origin-related exploration has been claimed to be phylogenetically conserved across the vertebrates. In the current study we use the same methodology to examine whether origin-related exploration has also been conserved in human pre-walking Typically-Developing (TD) and a group of Non-Typically Developing (NTD) infants in the presence of their stationary mother. The NTDs had been referred to a center for the early treatment of autism in infancy by pediatric neurologists and clinicians. The TDs established a reference place (origin) at mother's place, and exhibited a modular partitioning of their path into excursions performed in reference to mother, visiting her often, and reaching closely. In contrast, the NTDs did not establish a distinct origin at the mother’s place, or any other place, and did not partition the exploratory path into excursions. Once this difference is validated, the differences between the human infant groups may serve as an early referral tool for child development specialists. The absence of distinct modularity in human infants at risk of autism spectrum disorder can guide the search for animal models for this disorder in translational research.